Telaah Ayat-Ayat Hukum Keluarga Perspektif Gender Kritik Terhadap Pemahaman Feminis Muslim - Nur Yasin (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT The Qur'an never divides men and women as discriminating couples to the disadvantage of one party. But the differences referred to in the Qur'an are a mere distinctive distinction. With this latter nature, the above distinctions really are a mutual distinction, affecting and benefiting one another (mutualism). The offer of feminist interpretation is apparently not fully holistic in its application because it still views men and women in discriminatory positions. It can not be denied above, there are some interpretations of the feminism that provide new enlightenment but still need to be reconstructed again. Keyword: Paragraphs Family Law, Criticism, Feminist, Gender.